The Constitution decoded : a guide to the document that shapes our nation - Kennedy, Katie, 1963- (Workman Publishing Company, 2020)
Extends an illustrated guide to the United States Constitution, explaining the original draft, the Bill of Rights, the twenty-seven amendments, and the declaration of independence. Provides text of the original drafts with notations that explain the meaning of each section. Includes a glossary, resources for further reading, and an index.